2007
DOI: 10.1681/asn.2006060625
|View full text |Cite
|
Sign up to set email alerts
|

Pax Transactivation-Domain Interacting Protein Is Required for Urine Concentration and Osmotolerance in Collecting Duct Epithelia

Abstract: Pax transactivation-domain interacting protein (PTIP) is a widely expressed nuclear protein that is essential for early embryonic development. PTIP was first identified on the basis of its interactions with the developmental regulator Pax2 but can also bind to other nuclear transcription factors. The Pax2 protein is essential for development of the renal epithelia and for regulating the response of mature collecting ducts to hyperosmotic stress. For determination of whether PTIP also functions in more differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Recent studies in which KMT cofactors were disrupted in the mature heart and kidney have shown that H3K4me3 is important in specific aspects of adult terminally differentiated tissues, such as cardiac electrophysiology and renal concentrating mechanisms. 42,43 Given its strong association with actively transcribed genes, the broad distribution of H3K4me3 and its KMT, Ash2l, in nephron progenitors and derivatives is not surprising. Our studies in clonal MM-like cells have demonstrated that H3K4me3 peaks decorate not only actively transcribed metabolic and housekeeping genes, but also promoters of developmental renal regulators such as Six2 and Osr1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in which KMT cofactors were disrupted in the mature heart and kidney have shown that H3K4me3 is important in specific aspects of adult terminally differentiated tissues, such as cardiac electrophysiology and renal concentrating mechanisms. 42,43 Given its strong association with actively transcribed genes, the broad distribution of H3K4me3 and its KMT, Ash2l, in nephron progenitors and derivatives is not surprising. Our studies in clonal MM-like cells have demonstrated that H3K4me3 peaks decorate not only actively transcribed metabolic and housekeeping genes, but also promoters of developmental renal regulators such as Six2 and Osr1.…”
Section: Discussionmentioning
confidence: 99%
“…Primary PTIP flox/flox MEFs were isolated from E13.5 embryos of PTIP conditional knock-out mice (26) and immortalized by transfection with pcDNA3 expressing SV40T following 3T3 protocol (27). Retrovirus infection of immortalized MEFs was performed as described (28).…”
Section: Methodsmentioning
confidence: 99%
“…Paxip1 f/f (Kim et al, 2007), TCRβ transgenic (Shinkai et al, 1993), and Lck Cre transgenic (Hennet et al, 1995) and S1PR1 transgenic (Liu et al, 2009) mice were generated as previously described. Rag2 −/− mice were obtained from Taconic Laboratories.…”
Section: Methodsmentioning
confidence: 99%